Cover, not caging, influences chronic physiological stress in a ground-nesting bird - Tan, Laura X. L.; Buchanan, Katherine L.; Maguire, Grainne S.; Weston, Michael A. (Journal of avian biology, 2015)
Predator exclosures (‘nest cages’) around nests are increasingly used to enhance hatching success of declining groundnesting birds. However, such exclosures are contentious and have been suggested to have detrimental effects on the species which they aim to protect. This study examines whether exclosures increase physiological stress of incubating birds, a hitherto unrecognised and untested potential drawback of exclosures. Red-capped plover Charadrius ruficapillus hatching success was radically altered and significantly higher for nests with exclosures (96.2%) compared with those without (6.8%). Chronic physiological stress in parents (as measured by the heterophil/lymphocyte [H/L] ratio in blood) did not vary between nests with and without exclosures, or between the sexes. However the absence of vegetative cover at the nest site was associated with a 62.7% elevation in H/L ratio, indicating that incubating birds which place their nests in the open are subject to increased levels of chronic stress. The results from this study demonstrate the fundamental importance of predation for the nesting success of this species and confirm that chronic stress levels are not a detrimental side effect of exclosure use.